Capacity Improvement and Protection of LTE Network on Ethernet Based Technique - Fadli Sirait; Akhmad Wahyu Dani; Triyanto Pangaribowo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
High demands for data rates in mobile communications is the reason for developing broadband wireless access technologies. Long Term Evolution (4G LTE) networks which offer significantly higher data rates and require suitably higher capacity backhaul networks. To prepare for the high data rates usage in 4G LTE, operators are using ethernet services in terms of backhaul connectivity. Protection packet switching developed to anticipated network failure on ethernet based network technology. The failures in the network include the link fails to connect to each network element, the network element fails to transfer the data to the destination, or the quality drops below the standard. In this paper we used two ethernet based technique, namely Ethernet over SDH and MPLS-TP with ring protection to anticipated network failure on these techniques. Furthermore, we measured performance of network by measuring and comparing the throughput, latency and jitter between Ethernet over SDH and MPLS-TP. We used bandwidth capacity 240 Mbps as plant bandwidth link and worked in MIMO 2 2. The results of measurements indicated that MPLS-TP with ring protection is the best technique to enhanced the performance of LTE network.